2006
DOI: 10.1504/ijbra.2006.010603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hair cycle-associated genes from time-course gene expression profile using fractal analysis

Abstract: Microarray technology permits one to monitor thousands of processes going on inside the cell. This tool has been used to study gene expression profiles associated with the hair-growth cycle. We provide a novel method called the fractal analysis method to identify hair-growth cycle associated genes from time course gene expression profiles. Fractal analysis is a much better method than the computational method used by Lin et al. (2004). The fractal dimension obtained by fractal analysis process also indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…During the following cycles, synchronous HF growth occurs only in relatively small patches , thus demonstrating a spatially restricted correlation radius. This phenomenological observation was supported by time‐course experiments looking at gene expression profile data . Such specific spatiotemporal HF behaviour leads to production of a mosaic skin pattern with HFs belonging to a single patch being quasi‐synchronized in the same phase of the cycle.…”
Section: Introductionmentioning
confidence: 67%
“…During the following cycles, synchronous HF growth occurs only in relatively small patches , thus demonstrating a spatially restricted correlation radius. This phenomenological observation was supported by time‐course experiments looking at gene expression profile data . Such specific spatiotemporal HF behaviour leads to production of a mosaic skin pattern with HFs belonging to a single patch being quasi‐synchronized in the same phase of the cycle.…”
Section: Introductionmentioning
confidence: 67%
“…Vélez et al reported the possible use of multifractals in the measurement of local variations in DNA sequence in order to define the structure-function relationship in chromosomes [41], and Mathur et al used fractal analysis of gene expression in studying the hair growth cycle. Moreover [42], fractal genomics modeling has been used to predict new factors in signaling pathways and the networks operating in neurodegenerative disorders [43]. At the cellular level, fractal dimension was used in evaluating the morphological diversity of neurons and discriminating them on the basis of the neuronal extensions [44]; fractals can also explain higher orders of organization in biological materials such as the organization of tissues [45] and branching of tubular systems such as the respiratory and the vascular systems [46-49].…”
Section: Methodsmentioning
confidence: 99%